Chemical Characteristics of Ultisols and Purple Eggplant Yields due to the Application of Composted Paper Sludge and NPK Fertilizer - Yayu Agustini, Rika; Liska Mutiara Septiana; Aliya Azkia Zahra (Jurnal Ilmu Pertanian Indonesia, 2026)
Paper sludge is waste that has the potential to be used as a soil ameliorant to improve soils with low fertility levels, such as Ultisols. This study aimed to evaluate the impact of applying composted paper sludge and NPK fertilizer on selected chemical properties of Ultisols, including pH, total nitrogen, total phosphorus, and total potassium, as well as on the yield of purple eggplant. The study used seven treatments consisting of sludge doses of 10, 20, and 30 tons/ha in combination with NPK fertilizer doses of 150 and 300 kg/ha. The results showed that the application of composted paper sludge and NPK fertilizer improved the chemical properties of Ultisols, with total-N (0.47%), total-P (0.16%), and total-K (0.03%) increasing, as well as producing the best results in terms of number of fruits (6), fruit length (31.00 cm), and fruit weight (268.20 g). The best combination for improving soil chemical properties was obtained from the treatment of 30 tons/ha of composted paper sludge with 300 kg/ha of NPK fertilizer, while the best combination for increasing purple eggplant yields was obtained from the treatment of 30 tons/ha of composted paper sludge with 150 kg/ha of NPK fertilizer. The application of composted paper sludge as a soil ameliorant promoted fertility in Ultisols. In addition, the more composted paper sludge applied, the more positive the effect on soil fertility and purple eggplant yield was.Keywords: fertilizer, paper sludge, purple eggplant, ultisols, waste